Economic savings and costs of periodic mammographic screening in the workplace. - Griffiths, R; McGrath, M; Vogel, V (1996)
This article discusses the costs and benefits of mammographic screening in the workplace. The cost of mammography itself and of diagnostic work-up are two of the largest costs involved. Therefore, the most efficient approach to providing mammography depends on the number of employees receiving mammography; and the diagnostic accuracy of mammography and underlying incidence of breast cancer in the screened population strongly influence the number of suspicious mammograms that are not associated with breast cancer. The health benefit of mammographic screening is due to reduced mortality and morbidity through early detection and more effective treatment, which may also result in economic savings if early-stage cancer is less expensive to treat. However, the total lifetime cost of treating early-stage cancer may be greater than treating late-stage cancer because of improved survival of early-stage patients. Thus, although periodic mammographic screening is not likely to result in overall economic savings, in many populations of working-age women, especially those with identifiable risk factors, screening is cost-effective because the expenditure required to save a year of life through early detection of breast cancer is low compared to other types of health services for which employers commonly pay.